How to do nothing : resisting the attention economy - Odell, Jenny (Multimedia artist) (Melville House, 2019)
"When the technologies we use every day collapse our experiences into 24/7 availability, platforms for personal branding, and products to be monetized, nothing can be quite so radical as . . . doing nothing. Here, Jenny Odell sends up a flare from the heart of Silicon Valley, delivering an action plan to resist capitalist narratives of productivity and techno-determinism, and to become more meaningfully connected in the process"--